Transmembrane segments of complement receptor 3 do not participate in cytotoxic activities but determine receptor structure required for action of Bordetella adenylate cyclase toxin - Wald, Tomas; Osickova, Adriana; Masin, Jiri; Liskova, Petra M; Petry-Podgorska, Inga; Matousek, Tomas; Sebo, Peter; Osicka, Radim (Pathogens and disease, 2016)
Adenylate cyclase toxin-hemolysin (CyaA, ACT or AC-Hly) of the whooping cough agent Bordetella pertussis penetrates phagocytes expressing the integrin complement receptor 3 (CR3, CD11b/CD18, α(M)β(2) or Mac-1). CyaA translocates its adenylate cyclase (AC) enzyme domain into cell cytosol and catalyzes unregulated conversion of ATP to cAMP, thereby subverting cellular signaling. In parallel, CyaA forms small cation-selective membrane pores that permeabilize cells for potassium efflux, contributing to cytotoxicity of CyaA and eventually provoking colloid-osmotic cell lysis. To investigate whether the single-pass α-helical transmembrane segments of CR3 subunits CD11b and CD18 do directly participate in AC domain translocation and/or pore formation by the toxin, we expressed in CHO cells variants of CR3 that contained artificial transmembrane segments, or lacked the transmembrane segment(s) at all. The results demonstrate that the transmembrane segments of CR3 are not directly involved in the cytotoxic activities of CyaA but serve for maintaining CR3 in a conformation that is required for efficient toxin binding and action.
Keywords: Animals; biologický transport; AMP cyklický; CD18 Antigens; makrofágový antigen 1; buněčné linie; CHO buňky; Phagocytes; CD11b Antigen; adenylate cyclase toxin; Adenylate Cyclase Toxin; Bordetella pertussis; lidé; signální transdukce; adenosintrifosfát; complement receptor 3; fagocyty; Signal Transduction; ICP-MS; Cricetulus; Cell Line; transmembrane segment; Biological Transport; CyaA; Cyclic AMP; Macrophage-1 Antigen; Adenosine Triphosphate; CD11b/CD18; zvířata; antigeny CD18; antigeny CD11b; adenylátcyklasový toxin; CHO Cells; Humans